2021
DOI: 10.1088/1361-665x/abdc08
|View full text |Cite
|
Sign up to set email alerts
|

Timber moisture detection using wavelet packet decomposition and convolutional neural network

Abstract: As timber structures are vulnerable to degradation due to the tendency to trap moisture, the present study proposed a new percussion-based method to replace the existing constant contact between structures and sensors. A total of two approaches have been proposed to automated detect the moisture content (MC) of timber: (a) the random forest classifier (machine learning-based) was employed to classify the wavelet packet decomposition (WPD) features extracted from excitation-induced sound signals (WPD + RF); and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…These drawbacks make conventional SHM methods not convenient for large‐scale industrial applications. It is found that machine learning shows great potential in structural health monitoring (SHM) 11–17 . For simplification, Kong et al 18 proposed a percussion‐based nondestructive method to detect the health condition of bolted joints by using the machine learning method.…”
Section: Introductionmentioning
confidence: 99%
“…These drawbacks make conventional SHM methods not convenient for large‐scale industrial applications. It is found that machine learning shows great potential in structural health monitoring (SHM) 11–17 . For simplification, Kong et al 18 proposed a percussion‐based nondestructive method to detect the health condition of bolted joints by using the machine learning method.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] However, the application of sensorbased acquisition networks can be prohibitively timeconsuming and labour-intensive, and long-term monitoring may prove impractical due to the need to store massive amounts of data. [26][27][28][29][30] Machine learning in computer vision demonstrated rapidity and reliability for conducting image-based inspection of the concrete surface. 8,[31][32][33][34][35][36] Deep learning with robustness against noise disturbance has been applied to accurately interpret images and sensing data for crack detection.…”
Section: Introductionmentioning
confidence: 99%
“…2325 However, the application of sensor-based acquisition networks can be prohibitively time-consuming and labour-intensive, and long-term monitoring may prove impractical due to the need to store massive amounts of data. 2630…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid improvement of engineered wood products, timber has also been widely constructed for tall buildings and long-span structures which offers more functions in human society. [1][2][3] However, timber is a biomass construction material, resulting that its mechanical properties are highly influenced by environmental variations and biological actions. Internal cavity eroded by termites is a common degradation pattern, that may cause unexpected structural failures of timber structures.…”
Section: Introductionmentioning
confidence: 99%